Rustrela virus infection – An emerging neuropathogen of red‐necked wallabies (Macropus rufogriseus). Issue 6 (29th September 2022) - Voss, Anne; Schlieben, Patricia; Gerst, Sascha; Wylezich, Claudia; Pfaff, Florian; Langner, Christoph; Niesler, Michael; Schad, Petra; Beer, Martin; Rubbenstroth, Dennis; Breithaupt, Angele; Mundhenk, Lars
Summary: The rustrela virus (RusV) was recently described as a novel pathogen in a circumscribed area of northern Germany close to the Baltic Sea. Up to now, the virus has been detected in cases of fatal non‐suppurative meningoencephalitis in zoo animals of different species and a single wild carnivore as well as in apparently healthy yellow‐necked field mice ( Apodemus flavicollis ). Data regarding the background of this previously undiscovered pathogen, including clinical presentation of the disease, host range and distribution of the virus, are still limited. Here, three euthanized red‐necked wallabies ( Macropus rufogriseus ) from zoos of different areas in northeastern Germany were submitted for necropsy after presenting with apathy and therapeutically unresponsive neurological signs. A moderate to severe, non‐suppurative meningoencephalitis was diagnosed in all three cases. RusV was consistently detected via RT‐qPCR and RNA in situ hybridization in the brains of all wallabies. Other commonly known neuropathogens could not be detected.